Obtaining plant models for formal verification tasks from 3D CAD models: which is the best approach? - Lobo, Edgar (2013)
The use of analysis techniques for industrial controller’s analysis, such as Simulation and Formal Verification, is sometimes complex on industrial context. This complexity is due to the fact that such techniques require sometimes big investment in highly qualified human resources that have sufficient theoretical knowledge in those domains. This paper aims, mainly, to show that it is possible to improve the implementation and industrial using of such techniques, by facilitating their application. As any mechatronic system needs to be modeled by using CAD models, these models could be used, in a systematic way, by these companies in order to increase the use of such techniques for the analysis of industrial controllers. For this purpose, it is discussed, in the paper, the best way to systematize these procedures, and this paper describes, only, the first step of a complex process and promotes a discussion of the main difficulties that can be found and a possibility for handle those difficulties is presented. A case study is presented in order to illustrate how to obtain a plant model for formal verification purposes from an original 3D CAD model.